THE ACQUISITION OF RUSSIAN GRAMMAR CASES BY BRAZILIAN STUDENTS - Sabadin Santos T. Medina, Joao Paulo; Budnik, Ekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The analysis of Russian discourse in the proficiency levels B1 and B2 points out to Brazilian students' assimilation problems regarding the grammar cases. Such problems are interpreted based on the structural comparison between the verb-object relations in Portuguese and Russian: - the verb and object may be connected directly or through a preposition; - the meaning is also intermediated by the grammar cases. To establish interlinguistic equivalents, they are compared structures with similar meaning in the native language compared to the learnt one. The research aims to understand through an empirical approach to Brazilian students' difficulties when learning grammar cases regarding their native language interference. The authors recorded interviews with Brazilian students in the referred proficiency levels, which were considered under the typological comparison; a questionary answered by the same students was then implemented to confirm such difficulties. The results indicate the structural divergence and consequent difficulty of Brazilian students to acquire the Dative and the Instrumental cases when a preposition does not intermediate the verb-object relation.